THE RELATIONSHIP BETWEEN LEADERSHIP OF ADMINISTRATORS AND WORKING MOTIVATION OF TEACHERS IN EDUCATIONAL OPPORTUNITY EXPANSION SCHOOLS UNDER CHAIYAPHUM PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Boonphum, Supansa; Piampuechana, Niyada (Journal of Buddhist Education and Research (JBER), 2022)
The objectives of this research were: 1) to study leadership of administrators in educational opportunity expansion schools under Chaiyaphum Primary Educational Service Area Office 1, 2) to study working motivation of teachers in educational opportunity expansion schools under Chaiyaphum Primary Educational Service Area Office 1 and 3) to study relationship between leadership of administrators and working motivation of teachers in educational opportunity expansion schools under Chaiyaphum Primary Educational Service Area Office 1. The sample group consisted of administrators and teachers, with total number of 265 people. The research tool used for data collection was a 5-level rating scale questionnaire. The statistics used in data analysis comprised percentage, mean, standard deviation and Pearson's Simple Correlation. The research results were found that: The leadership of administrators in educational opportunity expansion schools under Chaiyaphum Primary Educational Service Area Office 1, in overall, was rated at a high level. When considering each aspect, it was found that the aspect with the highest level of practice was team leadership, followed by output leadership, the aspect with the lowest level of practice was middle of the road leadership. Working motivation of teachers in educational opportunity expansion schools under Chaiyaphum Primary Educational Service Area Office 1, in overall, was rated at a high level. When considering each aspect, it was found that the aspect with the highest level of practice was the need for relationship, followed by the need for survival, the aspect with the lowest level of practice was the need for career advancement. The relationship between leadership of administrators and working motivation of teachers in educational opportunity expansion schools under Chaiyaphum Primary Educational Service Area Office 1, in overall, was positive and at a high level with the statistically significant level of 0.01.